2014
DOI: 10.1007/s10608-014-9648-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Anxiety Sensitivity and Difficulties in Emotion Regulation: An Examination Among Individuals in Residential Substance Use Treatment with Comorbid Posttraumatic Stress Disorder

Abstract: Individuals with posttraumatic stress disorder (PTSD) exhibit deficits in cognitive and emotional processes. PTSD severity is positively associated with anxiety sensitivity (AS) and difficulties in emotion regulation, and difficulties in emotion regulation mediate the relation between AS and PTSD. However, previous research has not examined the interactive nature of these variables. Associations between PTSD, AS, and difficulties in emotion regulation were examined in patients with PTSD in a residential substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Improvements in trauma‐coping self‐efficacy and emotion regulation are consistent with prior findings indicating that these outcomes improve following exposure therapy among individuals with PTSD‐SUD 20,33,34 . Improvements in recovery capital scores suggest that participants felt more positively about SUD recovery post‐WET 35 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Improvements in trauma‐coping self‐efficacy and emotion regulation are consistent with prior findings indicating that these outcomes improve following exposure therapy among individuals with PTSD‐SUD 20,33,34 . Improvements in recovery capital scores suggest that participants felt more positively about SUD recovery post‐WET 35 .…”
Section: Discussionsupporting
confidence: 84%
“…These findings are consistent with published reports indicating that PTSD can be treated concurrently with SUD and that exposure-based interventions are most effective 6,7,11 Improvements in trauma-coping self-efficacy and emotion regulation are consistent with prior findings indicating that these outcomes improve following exposure therapy among individuals with PTSD-SUD. 20,33,34 Improvements in recovery capital scores suggest that participants felt more positively about SUD recovery post-WET. 35 Overall, results suggest that WET is associated with improvements in mental health indicators important to PTSD-SUD recovery, in addition to PTSD symptom reduction.…”
Section: Mental Health Indicatorsmentioning
confidence: 99%
“…A common method of operationalizing the construct of emotion regulation difficulties distinguishes six subfactors: emotional nonacceptance, difficulties in goal directed behavior, low emotional awareness, low emotional clarity, impulse control difficulties, and limited access to emotion regulation strategies (Gratz & Roemer, 2004). Moreover, across various demographic samples, difficulties in emotion regulation are implicated in the development of mental health problems, including depression (Joormann & Stanton, 2016; Tully et al, 2016; Van Beveren et al, 2016), suicidality (Gratz & Roemer, 2004), and anxiety (Sippel et al, 2015). In line with this work, difficulties in emotion regulation relate to greater levels of negative affect among both non-Latino (Kashdan et al, 2008) and Latino/a adults (Archuleta & Lakhwani, 2016; Paulus et al, 2016).…”
Section: Explaining the Acculturative Stress–affective Symptomology Linkmentioning
confidence: 99%
“…The DERS has been used extensively in many different populations, spanning adult and adolescent age groups. It has been used with veterans (Sippel et al, 2015), community adults (Lilly et al, 2014), college students (O'Bryan, McLeish, Kraemer, & Fleming, 2015), outpatients (Khosravani et al, 2017), and inpatients (Fowler et al, 2014;Perez et al, 2012;Sippel et al, 2015). However, with 36 items and some over-lapping item content, it may be overly lengthy or redundant for some research questions or samples, and some studies have identified problems with its purported latent factor structure (Bardeen, Fergus, & Orcutt, 2012;Miguel, Giromini, Colombarolli, Zuanazzi, & Zennaro, 2017).…”
Section: Introductionmentioning
confidence: 99%